Analisis K3 Operator Slitter Machine dengan Pendekatan Job Safety Analysis di PT ABC - Lumbantoruan, Winda D; Herwanto , Dene (Fakultas Teknik Universitas Tulang Bawang, 2025)
Occupational health and safety (OHS) is a critical aspect of industrial production processes, particularly at PT. ABC, which operates high-risk machinery such as the slitter machine. This machine plays an essential role in the process of cutting cardboard, but its use poses significant risks of workplace accidents. This study aims to analyze the occupational health and safety controls for slitter machine operators at PT. ABC using the Job Safety Analysis (JSA) method. The slitter machine is crucial in the cardboard production process but carries a high risk of accidents. This study identifies potential hazards, evaluates risks, and recommends control measures to minimize the risk of accidents. The results show that there are various levels of risk, from low to high, involving serious injuries such as bone fractures and amputations. Suggested improvements include the use of personal protective equipment (PPE) and support tools like handlifts to enhance workplace safety. The implementation of JSA is expected to reduce workplace accident risks and improve the company's operational efficiency. Keywords: Job Safety Analysis, Occupational Safety, Slitter Machine